Moving forward [compact disc] - Williams, Bernie, 1968- (Reform Records, 2009)
Critically acclaimed guitarist, and former New York Yankees star, Bernie Williams returns with his second album. Included are collaborations with Jon Secada and Bruce Springsteen.